Conditioning of hiPSC-derived cardiomyocytes using surface topography obtained with high throughput technology. (7th September 2021) - Cortella, Lucas R X; Cestari, Idágene A; Lahuerta, Ricardo D; Araña, Matheus C; Soldera, Marcos; Rank, Andreas; Lasagni, Andrés F; Cestari, Ismar N
Abstract: Surface functionalization of polymers aims to introduce novel properties that favor bioactive responses. We have investigated the possibility of surface functionalization of polyethylene terephthalate (PET) sheets by the combination of laser ablation with hot embossing and the application of such techniques in the field of stem cell research. We investigated the response of human induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) to topography in the low micrometer range. HiPSC-CMs are expected to offer new therapeutic tools for myocardial replacement or regeneration after an infarct or other causes of cardiac tissue loss. However, hiPSC-CMs are phenotypically immature compared to myocytes in the adult myocardium, hampering their clinical application. We aimed to develop and test a high-throughput technique for surface structuring that would improve hiPSC-CMs structural maturation. We used laser ablation with a ps-laser source in combination with nanoimprint lithography to fabricate large areas of homogeneous micron- to submicron line-like pattern with a spatial period of 3 µm on the PET surface. We evaluated cell morphology, alignment, sarcomeric myofibrils assembly, and calcium transients to evaluate phenotypic changes associated with culturing hiPSC-CMs on functionalized PET. Surface functionalization through hot embossing was able to generate, at low cost, low micrometer features on the PET surface that influenced the hiPSC-CMs phenotype, suggesting improved structural and functional maturation. This technique may be relevant for high-throughput technologies that require conditioning of hiPSC-CMs and may be useful for the production of these cells for drug screening and disease modeling applications with lower costs.